STRUKTUR DAN FUNGSI TEKS LAGU POP BALI BERTEMA SOSIAL KARYA ANAK AGUNG RAKA SIDAN - Ariana, I Putu (Humanis, 2013)
The research of Balinese social – themed pop-song text by Anak Agung Raka Sidan is aimed to describe the elements and the function of the text song itself.. In the term of data supplied by using observational method which is also helped by noticing and translating techniques. In the analysis phase used qualitative methods in the manner of descriptive – analytic technique. The result of the analysis is presented by using informal methods which is assisted by deductive and inductive techniques. The result that is obtained in this research is the Balinese social-themed pop-song text by Anak Agung Raka Sidan has a similar form to the poetry, so that the song text has the nature and formation method. The nature of the song text included the theme, sense, tone and trusteeship whereas the formation method included the diction, imagination, real word, figure of speech, and also the rhythm and rhyme. The function of Balinese social-themed pop-song text by Anak Agung Raka Sidan is divided into four functions, such as esthetic function, education function, social function, and economical function.
Keywords: song text, structure and function